Posterior reversible encephalopathy syndrome in a young male with IgA nephropathy and chronic kidney disease: a case report from the Maldives - Rajib Kumar Dey; Gunjan Khadka; Shifa Ishaq; Aishath Zeena Abdul Jaleel; Aminath Shafeenaz Moosa; Saifullah Muslim; Ali Nazeem (The Egyptian Journal of Internal Medicine)
Abstract Background Posterior reversible encephalopathy syndrome (PRES) is a clinico-radiological condition which is commonly associated with chronic kidney disease (CKD), hypertensive encephalopathy, eclampsia, and the use of cytotoxic drugs. It can cause vasogenic edema of the brain and is characterized by nausea, vomiting, headache, seizures, visual changes, and other focal neurological deficits. Acute hypertension is a predisposing factor for PRES which can occur in CKD patients due to fluid overload. Uremia in CKD patients is also one of the factors for developing PRES. Neuroimaging findings involve posterior white matter edema commonly affecting the parietal and occipital lobes. However, involvement of a non-posterior distribution, mainly in watershed areas, including within the frontal, inferior temporal, cerebellar, and brainstem regions, has been reported. Case presentation This case report discusses a case of a 27-year-old male with underlying IgA nephropathy, who presented with generalized throbbing headache, along with 1-day history of nausea and vomiting. This was followed by blurring of vision and 2 episodes of abnormal jerky movements of the body on the first day of admission. On examination, he was found to be hypertensive with no focal neurological deficits. Magnetic resonance imaging (MRI) T2/fluid-attenuated inversion recovery (FLAIR) findings showed hyperintense areas on the right frontal periventricular and right parietal and bilateral occipitotemporal lobes which was suggestive of PRES. The patient was treated with antiepileptics and antihypertensives and was started on dialysis following which his condition improved, and he was discharged in stable condition. Conclusion Symptoms of PRES are usually reversible unless cerebral hemorrhage or ischemia has occurred which can result in irreversible neurological deficit or death. Hence, it is crucial to identify and manage PRES promptly. Clinical suspicion and radiological findings aid in early diagnosis. It is also important to be aware of uncommon radiological findings (involvement of the right frontal periventricular area) as in our case.